The science and the art in the physical examination. - Luis Rodríguez Rivera (Medisur)
It is assumed that skills to fulfill physical examination stays in the conative sphere, not in the cognitive one. Only it is learnt how to do an adequate physical examination, doing it, and repeating it many times, with patients and healthy persons. Furthermore, the apprentice at the beginning needs the guidance and feedback of an expert. If semiological data are wrong, almost always there will be diagnostic mistakes. The successive steps of the exploration don´t have to be rigid and it will depend on each patient and doctor. It is referred that many errors are made during the physical examination, but they are frequently overlooked. At last, the doctor–patient relationship is very important in order to achieve an adequate physical exploration.